Immigrant Key Workers: Their Contribution to Europe's COVID-19 Response - Francesco Fasani; Jacopo Mazza (Institute of Labor Economics (IZA), 2024)
This paper contributes to the literature on the Covid-19 effects on workers and labor markets by focusing on the experience of migrant key workers in EU countries. Our analysis, based on survey data on more than 3 million workers, explores three main aspects. First, we document the over-representation of migrant workers in key occupations, particularly in low-qualified roles. Second, we examine the selection into key occupations. According to our estimates, women are more likely to be key workers, the relationship with education is V-shaped, and EU and Extra EU migrants are, respectively, 12 and 15 percent more likely to be key workers than comparable natives. Finally, we estimate the impact of Covid-19 on the labor market, showing that migrant key workers had to extend their working hours during the pandemic and, nevertheless, faced a 2-3 times higher probability of being laid off relative to natives. Our findings imply that migrant workers played a crucial role in the response to the pandemic, but endured a harsher fate than native workers.
Keywords: F22; J61; K37; 330; migrant workers; COVID-19; essential occupations